A background Ca 2+ entry pathway mediated by TRPC1/TRPC4 is critical for development of pathological cardiac remodelling - Camacho Londoño, Juan E. (2015)
Aims: Pathological cardiac hypertrophy is a major predictor for the development of cardiac diseases. It is associated with chronic neurohumoral stimulation and with altered cardiac Ca2+ signalling in cardiomyocytes. TRPC proteins form agonist-induced cation channels, but their functional role for Ca2+ homeostasis in cardiomyocytes during fast cytosolic Ca2+ cycling and neurohumoral stimulation leading to hypertrophy is unknown. Methods and results: In a systematic analysis of multiple knockout mice using fluorescence imaging of electrically paced adult ventricular cardiomyocytes and Mn2+-quench microfluorimetry, we identified a background Ca2+ entry (BGCE) pathway that critically depends on TRPC1/C4 proteins but not others such as TRPC3/C6. Reduction of BGCE in TRPC1/C4-deficient cardiomyocytes lowers diastolic and systolic Ca2+ concentrations both, under basal conditions and under neurohumoral stimulation without affecting cardiac contractility measured in isolated hearts and in vivo. Neurohumoral-induced cardiac hypertrophy as well as the expression of foetal genes (ANP, BNP) and genes regulated by Ca2+-dependent signalling (RCAN1-4, myomaxin) was reduced in TRPC1/C4 knockout (DKO), but not in TRPC1- or TRPC4-single knockout mice. Pressure overload-induced hypertrophy and interstitial fibrosis were both ameliorated in TRPC1/C4-DKO mice, whereas they did not show alterations in other cardiovascular parameters contributing to systemic neurohumoral-induced hypertrophy such as renin secretion and blood pressure. Conclusions: The constitutively active TRPC1/C4-dependent BGCE fine-tunes Ca2+ cycling in beating adult cardiomyocytes. TRPC1/C4-gene inactivation protects against development of maladaptive cardiac remodelling without altering cardiac or extracardiac functions contributing to this pathogenesis.